Melaka Chitties: the story of the unique and colourful Melaka-born Hindu community - Muthusamy, Paramasivam; Karpaya, Narayanasamy (Universiti Putra Malaysia Press, 2017)
Assimilation and acculturation through the centuries have created some distinctly unique communities that have survived the challenges of time to survive till today in Malaysia. One such community is the Melaka Chitties that has origin from the Melaka Sultanate period, when the Tamil-Hindu traders from the Indian sub-continent were one of the many others, including the chinese, the Javanese and the Arabs who frequented Melaka in the fifteenth century. The distinct chitty community evolved through inter-marriage between the male traders and the local women, with a stauch adherence to Hinduism in their families. The Malay language, as the local language, was gradually adopted as its mother tongue by this emerging community that lived in Kampung Keling in Melaka. We present the story of this community, the cultural traits that it has retained through the centuries, its present position and the challenges that it is facing today. An integral part of the story of Malaysia.